The new alchemists : - Hazen, Robert M. (Times Books, 1993)
Looks at the discoveries of today's scientists, describing a sand experiment that sheds light on dinosaur extinction, how everyday gases become dense metals inside large planets, and how almost any carbon-rich mineral can be transformed into diamonds. 17,500 first printing.